Audit Committee, External Pressure, and Company Size: Key Factors in Detecting Fraudulent Financial Reporting - Anisa, Anisa; Damayanty, Aulia (Universitas Pamulang, 2025)
The research seeks to analyze the role of audit committees, external pressure, and company size in identifying fraudulent financial reporting, supported by empirical findings. The study adopts a descriptive design within a quantitative approach, where data is obtained through purposive sampling and processed using Eviews 12. The findings reveal that neither the audit committee nor the size of the company influences the detection of financial reporting fraud, while external pressure was proven to have an effect. These findings indicate that external pressure is an important factor that can increase the risk of fraudulent practices of financial statements, so company management and regulators need to pay attention to external pressure indicators in order to strengthen the company's control and governance systems.